2015
DOI: 10.1126/sciadv.1500019
|View full text |Cite
|
Sign up to set email alerts
|

Vocal learning in a social mammal: Demonstrated by isolation and playback experiments in bats

Abstract: Isolation and playback experiments demonstrate vocal learning in bats and reveal the learning mechanism by continuous recordings from birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
102
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(103 citation statements)
references
References 23 publications
1
102
0
Order By: Relevance
“…36), with 6 females, 5 pups, and 1 male in cage 1, and 4 females, 4 pups, 1 male, and 1 young (of unknown sex) in cage 2. The cages were continuously monitored for 75 days, with IR-sensitive cameras and omnidirectional electret ultrasound microphones (Avisoft-Bioacoustics Knowles FG-O; 2 microphones in each cage).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…36), with 6 females, 5 pups, and 1 male in cage 1, and 4 females, 4 pups, 1 male, and 1 young (of unknown sex) in cage 2. The cages were continuously monitored for 75 days, with IR-sensitive cameras and omnidirectional electret ultrasound microphones (Avisoft-Bioacoustics Knowles FG-O; 2 microphones in each cage).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we used the extremely social and vocal Egyptian fruit bat ( Rousettus aegyptiacus ) to elucidate some of the huge potential of information capacity in a mammalian vocal communication system. Egyptian fruit bats are social mammals, that aggregate in groups of dozens to thousands of individuals, can live to the age of at least 25 years35, and are capable of vocal learning36. We housed groups of bats in acoustically isolated chambers and continuously monitored them with video cameras and microphones around-the-clock.…”
mentioning
confidence: 99%
“…Bats have recently caught the attention of the field due to their potential for vocal learning, sophisticated social structure and diversity (Knörnschild, 2014). Two species in particular have recently shown promise for vocal learning; Phyllostomus discolor (Esser, 1994) and Rousettus aegypticaus (Prat et al, 2015). Studying the genomes of these species provides a great opportunity to pinpoint genetic loci and major evolutionary events that may be relevant for the emergence of vocal learning in mammals.…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, researchers at Tel Aviv University reported that Egyptian fruit bat pups isolated from their parents are slow to develop mature, adult-like vocalizations, suggesting the babies rely on some form of learning. In fact, when isolated pups were exposed to recordings of select low-frequency adult calls, the pups developed a bias toward low-frequency vocalizations (13).…”
Section: From the Shadowsmentioning
confidence: 99%